Procesi ustvarjanja kulturne dediščine - Fakin Bajec, Jasna (Etnolog. Nova vrsta (Ljubljana), 2020)
Voluntary work within associations can make a significant contribution to the development of an inclusive society, balanced development and knowledge transfer. These are also the main starting points of the Cultural Heritage Strategy 2020-2023 where, among other things, particular importance in integrated conservation is given to the inclusion of community practices. Taking the example of the activities of the Debela Griža Society in the Karst region and the inclusion of a private undertaking in the management of a prehistoric hillfort there, the article discusses the discrepancies in the practical implementation of integrated approaches. This is also reflected in the negation of what was achieved through voluntary work.
Keywords: Debela griža; dediščinska društva; Kras; kulturna dediščina; neoliberalizem; prostovoljno delo; Slovenci